Strain improvement to enhance the production of recombinant penicillin acylase in high-cell-density Escherichia coli cultures - Lin, Y. H.; Hsiao, H. C.; Chou, C. P. (Biotechnology Progress, 2002)
Using fed-batch operation for high-cell-density cultivation, efforts are frequently made for optimization of culture parameters, particularly feeding strategy. The current study also emphasized the importance of selecting strains for the production of recombinant proteins in high-cell-density cultures. With Escherichia coli penicillin acylase (PAC) as a target protein, the host/vector system of MDDeltaP7 harboring pTrcKnPAC2902 and pKS12 was designed for optimization of fed-batch cultivation for recombinant protein production. The host, MDDeltaP7, potentially had a high translational and periplasmic processing efficiency for pac expression. On the other hand, the vector, pTrcKnPAC2902, was genetically constructed for pac overexpression. Coexistence of the other vector, pKS12, significantly enhanced PAC production by improving cell physiology and reducing the amount of inclusion body formation upon pac overexpression. Am extremely high volumetric PAC activity at 37,500 U/L was obtained with the use of the developed host/vector system under optimum fed-batch culture conditions.